The leader : a political biography of Gough Whitlam - Walter, James, 1949- (St. Lucia, Qld. : University of Queensland Press, 1980)
"The number of books written about the Whitlam government and Whitlam himself have created a myth which continues to feed on itself. However, James Walter's approach in The Leader is quite unlike any previous commentator and is the only serious non-journalistic biography of the man. It is, in fact, unique in Australian political science as the first sustained attempt to apply psychological theory to the career of an Australian political leader."--Dust jacket.
Includes index.
Bibliography: p. [272]-286.
Keywords: Whitlam, Gough, -- 1916-2014.; Australia. Politics, 1972-1978. Whitlam, Gough, 1916-2014. Biographies; Premiers -- Australia -- Biography; Politics and Government - Political parties - Australian Labor Party; History - Political; History - Biographies; Politics and Government - Politicians; Australia -- Politics and government -- 1972-1975.; Australia